Case-Based Reasoning Research and Development 19th International Conference on Case-Based Reasoning, ICCBR 2011, London, UK, September 12-15, 2011. Proceedings - Ram, Ashwin; Wiratunga, Nirmalie; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 19th International Conference on Case-Based Reasoning, held in London, UK, in September 2011. The 32 contributions presented together with 3 invited talks were carefully reviewd and selected from 67 submissions. The presentations and posters covered a wide range of CBR topics of interest both to practitioners and researchers, including CBR methodology covering case representation, similarity, retrieval, and adaptation; provenance and maintenance; recommender systems; multi-agent collaborative systems; data mining; time series analysis; Web applications; knowledge management; legal reasoning; healthcare systems and planning systems.
Reasoning as Search: Supporting Reasoning with Distributed Memory -- Structure Mapping for Jeopardy! Clues -- Ontologies and Similarity -- Retrieval of Semantic Workflows with Knowledge Intensive Similarity Measures -- Qualitative vs. Quantitative Plan Diversity in Case-Based Planning -- On Dataset Complexity for Case Base Maintenance -- Improving Case Retrieval by Enrichment of the Domain Ontology -- Preference-Based CBR: First Steps toward a Methodological Framework -- How Many Cases Do You Need? Assessing and Predicting Case-Base Coverage -- A Case-Based Approach to Open-Ended Collective Agreement with Rational Ignorance -- Amalgam-Based Reuse for Multiagent Case-Based Reasoning -- The 4 Diabetes Support System: A Case Study in CBR Research and Development -- Learning More from Experience in Case-Based Reasoning -- Acquiring Adaptation Cases for Scientific Workflows -- Combining Expert Knowledge and Learning from Demonstration in Real-Time Strategy Games -- Selective Integration of Background Knowledge in TCBR Systems -- User Satisfaction in Long Term Group Recommendations -- Using Personality to Create Alliances in Group Recommender Systems -- Analogy-Making for Solving IQ Tests: A Logical View -- Using Case-Based Tests to Detect Gray Cygnets -- Recommending Case Bases: Applications in Social Web Search -- Measuring Similarity in Description Logics Using Refinement Operators -- Term Similarity and Weighting Framework for Text Representation -- Fast Subgraph Isomorphism Detection for Graph-Based Retrieval -- Representation, Indexing, and Retrieval of Biological Cases for Biologically Inspired Design -- Ontology-Aided Product Classification: A Nearest Neighbour Approach -- A Case-Based Reasoning Approach for Providing Machine Diagnosis from Service Reports -- CBR with Commonsense Reasoning and Structure Mapping: An Application to Mediation -- Comparison of Reuse Strategies for Case-Based Classification in Bioinformatics -- Integration of Sequence Learning and CBR for Complex Equipment Failure Prediction -- Time Series Case Based Reasoning for Image Categorisation -- CBRSHM ? A Case-Based Decision Support System for Semi-Automated Assessment of Structures in Terms of Structural Health Monitoring -- A Case Base Planning Approach for Dialogue Generation in Digital Movie Design -- Successful Performance via Decision Generalisation in No Limit Texas Hold?em -- Rule-Based Impact Propagation for Trace Replay.
Electronic reproduction.
Keywords: Computer science; Computer Communication Networks; Database management; Case-based reasoning -- Congresses; Electronic books